How Cynara cardunculus ecotypes affect the production of Castelo Branco PDO cheese : a case study - Cristóvão, Mário André Monteiro (2022)
Cheese manufacture is a way of preserving a very perishable food, milk. This product is a versatile food that offers various flavours and textures, making it a convenient food and a source of nutrients1. Last available data from Instituto Nacional de Estatística (INE) indicates that the annual dairy consumption reaches 1218 thousand tons in Portugal and the third more consumed dairy product is cheese, with 137 thousand tons per year2. In 2021, the world cheese trade was forecast to rise 4 % to hit the record of 3.6 million tonnes.